1999
DOI: 10.1124/mol.56.6.1346
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for the Inhibition of Acetylcholinesterases by Irinotecan (CPT-11)

Abstract: Irinotecan (CPT-11) is an anticancer drug that occasionally produces acute cholinergic side effects. Preliminary findings suggest that these are mediated through the inhibition of acetylcholinesterase (AChE). In this study, the inhibition of various AChEs by CPT-11 was studied. The lactone form of CPT-11 resulted in apparent noncompetitive inhibition of electric eel and both human recombinant and erythrocyte AChE with K(i) values of 0.065, 0.19, and 0.29 microM, respectively. The carboxylate form of CPT-11 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
53
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 28 publications
5
53
3
Order By: Relevance
“…As pointed out by the authors, these data are not consistent with our own results (Dodds & Rivory, 1999), and those of others using very similar systems in which values of 0.2 mM for the IC 50 have been consistently reported (Kawato et al, 1993;Rivory et al, 1996;Morton et al, 1999). In our most recent study, we demonstrated that CPT-11 is a potent inhibitor of AChE at clinically relevant concentrations and revealed its mechanism of inhibition as being instantly reversible and apparently non-competitive (Dodds & Rivory, 1999). On reading the paper by Blandizzi et al (2001), we could not explain the reported discrepancy.…”
contrasting
confidence: 89%
See 4 more Smart Citations
“…As pointed out by the authors, these data are not consistent with our own results (Dodds & Rivory, 1999), and those of others using very similar systems in which values of 0.2 mM for the IC 50 have been consistently reported (Kawato et al, 1993;Rivory et al, 1996;Morton et al, 1999). In our most recent study, we demonstrated that CPT-11 is a potent inhibitor of AChE at clinically relevant concentrations and revealed its mechanism of inhibition as being instantly reversible and apparently non-competitive (Dodds & Rivory, 1999). On reading the paper by Blandizzi et al (2001), we could not explain the reported discrepancy.…”
contrasting
confidence: 89%
“…However, despite the e orts made to reproduce our experiments on the in vitro acetylcholinesterase (AChE) assay, we note that these authors still fail to propose any convincing explanation accounting for the discrepancy between our data (Blandizzi et al, 2001) and their repeated observations (Dodds & Rivory, 1999). Therefore, it is conceivable that in vitro assays, carried out on puri®ed preparations of AChE extracted from various sources, do not o er su cient levels of reliability to allow a clear assessment of the putative anti-AChE properties of irinotecan.…”
contrasting
confidence: 73%
See 3 more Smart Citations